The Median Nerve : Motor Conduction Studies - Gentili, Giuliano; Di Napoli, Mario (Springer International Publishing : Imprint: Springer, 2015)
This atlas systematically reviews motor conduction studies of the median nerve, from pilot human studies in peripheral nerve conduction during the 1950s through to the most recent scientific evidence. Descriptions are provided of a wealth of motor nerve conduction techniques that were reproduced in the laboratory, including both the originally proposed methods and variants. The techniques are organized according to practical criteria for ease of reference. Attention is focused especially on those techniques which have shown higher sensitivity and specificity in the diagnosis of compressive mononeuropathies like carpal tunnel syndrome (CTS)and on the most widely accepted guidelines, recommendations, quality measures, and electrodiagnostic classifications. The volume is completed with a detailed, well-illustrated glossary explaining the more commonly used terms in electrodiagnostic medicine (EDX). The atlas is primarily intended for residents and professionals in Neurology, as well as rehabilitation physicians and clinical neurophysiologists. The detailed descriptions of techniques and their practical use will also make the book an invaluable tool for novices and clinical neurophysiology technicians.